Modelling waves and near-shore circulation around the Cape Peninsula: towards enhanced predictions for South African coastal activities - de Vos, Marc (Department of Oceanography, 2023)
South Africa's coastal oceans support a multitude of human and ecological interests. My work at the confluence of academia, industry and government highlighted a gap in knowledge and capacity in the marine environmental information space. Broad research questions were developed and addressed through a combination of statistical review, data mining and numerical modelling: how do marine weather and oceanography impinge on South African coastal activities, what are the main circulation characteristics in a critical coastal region, and which environmental data are needed for predictions? Hazard modelling of environmental conditions and coastal user safety in South Africa revealed a wide sensitivity to weather-ocean hazards among different users and places. The Cape Peninsula sub-region exhibited the highest incident frequency related to increasing hazard severity. I implemented a coupled numerical ocean model (Delft3D FLOW and SWAN), with 700 m horizontal resolution to simulate waves and currents in this area. The model is driven by realistic forcing, striking a previously lacking balance between geographical coverage, spatial granularity, and process complexity. It has the potential to be deployed in forecast mode in future. Modelling confirmed the importance of wind in establishing broad circulation patterns and inducing nearshore upwelling. However, bay-scale cyclonic and anticyclonic flow in False Bay has low-medium predictability. These patterns developed as expected at times but failed to do so at others. The model's inclusion of two-way wave-current interactions enabled the identification of a novel cyclonic gyre in Table Bay during large wave events. Investigation revealed the gyre to be driven by wave induced radiation stress gradients. Model experiments with and without wave-coupling demonstrated that the gyre causes material differences in virtual drift trajectories and affects the monthly mean general circulation. This highlights its potential impact on coastal users and its implications for understanding Table Bay's circulation, where the importance of waves beyond the nearshore may be crucial for predictability. Enhanced velocity measurements, sufficient to resolve the alternating rotational circulation in False Bay and wave-driven gyre in Table Bay, are recommended. It is further suggested that appropriate wave forcing be included in any further circulation modelling in the study area.